2019
DOI: 10.21608/ejprs.2019.65115
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Autologous Nebulized Platelet Rich Plasma (PRP) As an Early Adjuvant Therapeutic and Prognostic Treatment Modality in the Management of Inhalation Lung Injury

Abstract: Background: Despite considerable advances in our knowledge of the pathophysiology of inhalation injury, there are few specific therapeutic options, and patient care is mainly supportive. Platelets release growth factors and other immune system components to start healing process. By using nebulized Platelet Rich Plasma (PRP), platelets may reduce inflammation and stimulates bronchial tree healing. However, there are no clear data supporting or refuting the use of inhaled PRP in inhalation injury. Objective: To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…A student's t-test and ANOVA were conducted, which showed the analysis of all measurements to be statistically significant (p-value was less than 0.05) [24]. Salama et al conducted a randomized controlled trial from 2015 to 2017 in order to assess the efficacy of nebulized autologous PRP in smoke inhalation patients [25]. The study included a total of 40: 20 in the study group and 20 acted as the control group [25].…”
Section: Review Resultsmentioning
confidence: 99%
“…A student's t-test and ANOVA were conducted, which showed the analysis of all measurements to be statistically significant (p-value was less than 0.05) [24]. Salama et al conducted a randomized controlled trial from 2015 to 2017 in order to assess the efficacy of nebulized autologous PRP in smoke inhalation patients [25]. The study included a total of 40: 20 in the study group and 20 acted as the control group [25].…”
Section: Review Resultsmentioning
confidence: 99%
“…The authors concluded that PRP proved to be beneficial for lung inflammation and did not present biosecurity problems [ 72 ]. In addition to preclinical studies, a clinical study was conducted on burnt patients with airway disease [ 73 ]. This prospective study included 40 patients with 25–50% burns and inhalation lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with inhalation lung injury Aerosolized PRP Lower extubation time, hospital stay and mortality rate [73] The platelet action is key in respiratory infections, and it can both improve the disease and aggravate the patient's condition. Therefore, the balance in their functions is crucial in the evolution of the disease.…”
Section: Horses With Inflammatory Airway Disease Intrabronchial Instimentioning
confidence: 99%
“…Significant resolution compared to the previous examination results suggest a significant improvement in radiological images in group A after treatment secondary to the stem cell effect on reducing inflammation and stimulating the pulmonological healing process. This method is already being used as a treatment option for lung inflammation via nebulization, with an increase in the number of lungs' endothelial cells, accelerating airway healing and favorably altering the pathophysiological changes [23]. Few stem cell therapy trials have been reported, most of which were performed by intravenous injection techniques and not by nebulization.…”
Section: Discussionmentioning
confidence: 99%